Thick electrodes upon biomass-derivative carbon current collectors: High-areal capacity positive electrodes for aluminum-ion batteries. (10th November 2019) - Chen, Ya; Zhou, Zhili; Li, Na; Jiao, Shuqiang; Chen, Haosen; Song, Wei-Li; Fang, Daining
Abstract: Rechargeable aluminum-ion batteries (AIBs) are considered as low-cost safe energy storage devices beyond lithium-ion batteries, due to the high volumetric capacity and rich abundance of aluminum. However, the highly corrosive room temperature ionic liquid electrolyte causes serious problems in the traditional metal current collectors, and electrochemical inert metals with higher density have been commonly used, which leads to dramatic decreased material utilization in the positive electrode. For addressing such issues, here a biomass-derivative carbon (BDC) current collector is demonstrated to construct millimeter-scale thick positive electrodes based on two types of graphite active materials (with different planar sizes) and two electrode configurations. The results suggest the strategy of using single-side casting process with graphite of smaller planar size would be more promising to promote the overall electrochemical properties and energy storage performance. The as-assembled thick electrode (with thickness up to ∼2 mm) using the same type of graphite is able to deliver much enlarged areal loading (36 mg cm −2 ), showing greater areal capacity for energy storage. The strategy and mechanism in this work offers a considerable approach for improving the current collectors and promoting the graphite proportion in AIBs. Graphical abstract: Image 1 Highlights: Millimeter-scale thick positive electrodes for aluminum-ion batteries. Enhanced performance using single-side casting process and small-size graphite. Addressing the issues of corrosion in the metal current collectors.